In situ Measuring Film-Depth-Dependent Light Absorption Spectra for Organic Photovoltaics - Feng, Xiang; Wang, Yuheng; Xiao, Tong; Shen, Zichao; Ren, Yurong; Lu, Guanghao; Bu, Laju (Frontiers in Chemistry, 2020)
Organic donor:acceptor bulk heterojunction are attracting wide interests for solar cell applications due to solution processability, mechanical flexibility and low cost. The photovoltaic performance of such thin film is strongly dependent on vertical phase separation of each component. Although film-depth-dependent light absorption spectra measured by non-in-situ methods have been used to investigate the film-depth profiling of organic semiconducting thin films, the in-situ measurement is still not well resolved. In this work, we propose an in-situ measurement method in combination with a self-developed in-situ instrument which integrates a capacitive coupled plasma generator, a light source and a spectrometer. This in-situ method and instrument are easily accessible and easily equipped in laboratories of the organic electronics, which could be used to conveniently investigate the film-depth-dependent optical and electronic properties.